Water in type I chondrules of Paris CM chondrite. (15th February 2017) - Stephant, A.; Remusat, L.; Robert, F.
Abstract: Hydrogen isotopic ratio and water concentration have been measured with the NanoSIMS in olivine, pyroxene and mesostasis in individual chondrules from the carbonaceous chondrites Paris (CM2), Renazzo (CR2) and ordinary chondrite Bishunpur (LL3). On average, chondrule pyroxenes in Renazzo, Bishunpur and Paris contain 893 ± 637 ppm (1SD), 879 ± 536 ppm and 791 ± 227 ppm H2 O, respectively. Concentration of H2 O in Chondrule olivines from Renazzo and Bishunpur is 156 ± 44 ppm and 222 ± 123 ppm, respectively. Olivines in the Paris chondrules have high water concentration (603 ± 145–1051 ± 253 ppm H2 O) with a minimum mean value of 645 ± 99 ppm. δD ranges from −212 ± 125‰ to 15 ± 156‰ and from −166 ± 133‰ to 137 ± 176‰ in Renazzo and Bishunpur chondrule olivines, pyroxenes and mesostases, respectively. In Paris chondrules, δD ranges from −398 ± 23‰ to 366 ± 35‰; this represents an extreme variation over 764‰. Paris olivines and pyroxenes are either enriched or depleted in deuterium relative to the mesostasis and no systematic isotopic pattern is observed. Simple model of chondrules hydration during parent body hydrothermal alteration is difficult to reconcile with such isotopic heterogeneity. It is proposed that a hydrous component, having a δD of c.a. −400‰, in the chondrule precursors, has been outgassed at 800–900 °C in the gas phase. Nevertheless, a residual water fraction remains trapped in Paris chondrules. Quantitative modeling supports this scenario.